Dissolução parcial de sociedade limitada por retirada e exclusão de sócio e a consequente apuração de haveres à luz do CPC/2015 - Pereira, Cristiano Padial Fogaça (2018)
This essay scrolls through several partial dissolution’s possibilities of limited liability companies arising out of exclusion or withdrawn of an entity member, until reaching the corporate property valuation and its different kinds of technical criteria, like the free cash flow analysis. This dissertation text also examines articles from the new Brazilian Code of Civil Procedure, especially the articles 599 to 609. Thus, an issue that involves different kinds of valuation criteria is analyzed by legal theories such as the principle of proportionality and the economic analysis of law